New media political engagement and participation in Malaysia - Chinnasamy, Sara (Politics in Asia series, 2018)
Analyses the exponential growth of independent news portal (INPs) in Malaysia and discusses the extent of impacts generated from these portals in Malaysian electoral conduct especially during Malaysia's 12th and 13th general elections. The interviews conducted for this book provide deeper insights from those producing news and at the same time provide a specific and thorough observation on political events including representatives of the Malaysian middle class.